EVALUATION ANTIBACTERIAL AND ANTIBIOFILM ACTIVITY OF Cymbopogon citrates L. ON FIMA AND PAPC GENES AGAINST Escherichia coli - Khalaf, Maha A.; AL-Azawi, A. H. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed  to evaluated the antibacterial activity on Cymbopogon citrates ( C. citrates ) leaves extract and assessment of its effect on fimA and papC genes in Escherichia coli ( E.coli )isolates. Rotery apparatus were used to prepare aqueous and methanolic extract; total phenolic content and high-performance liquid chromatography (HPLC) were conducted to determine the active compounds in the extract. The results showed that the methanolic and aqueous extracts contain seven flavonoids derivatives ( Catechine , Chlorogenic acid , Ferulic acid , Gallic acid , P-Coumaric acid , Qurcetine and Kaempferol ) in varies ration were identified on the basis of matching retention time with the standards. The total phenolic contents were 19.56 and 47.45 mg/g in 50 mg/ml, in aqueous and methanolic extracts respectively. The antibacterial activity of C. citrates leaves extracts showed that the aqueous extract was less effective than  methanolic extract in concentration 16 mg/ml. Moreover, the result of the minimum inhibitory concentration (MIC) showed that the methanolic extract on E.coli isolates was 16 mg/ml, while the MIC values of aqueous extract were 32 mg/ml. C. citrates methanolic leaves extract had antibiofilm activity, which inhibits 90% and 100% of the biofilm formation of E. coli in concentrations 16 and 32 mg/ml respectively. The result of the gene expression revealed that there is a decrease in the expression of the fimA and papC genes.